Tourism and leisure : current issues and perspectives of development - Pechlaner, Harald; Smeral, Egon (Springer Fachmedien Wiesbaden Imprint: Springer Gabler, 2015)
The Festschrift in honor of Prof. Dr. Peter Keller, president of the International Association of Scientific Experts in Tourism (AIEST) since 1994, represents a wide range of tourism research as well as the current state of the ongoing debates in tourism as a scientific research field. The aim is to cover multiple topics and trends in travelling and to discuss future development possibilities in the leisure industry. Contents Trends in Tourism and Leisure Future Development of Business Environment in Tourism Organization of Innovations in Tourism and Leisure Tourism Economics Target Groups Lecturers and students in the fields of tourism and leisure, regional development, and marketing Practitioners in tourism The Editors Prof. Dr. Harald Pechlaner holds the Chair of Tourism and is the head of the Center for Entrepreneurship at the Catholic University of Eichstaett-Ingolstadt. Prof. Dr. Egon Smeral is economist at the Austrian Institute of Economic Research (WIFO) in Vienna and lecturer on tourism and leisure economics.  .